Agroedutourism Model to Improve Environmental Awareness of Students in Some Elementary School in Malang Raya, East Java - Hanin Niswatul Fauziah; Endang Arisoesilaningsih; Bagyo Yanuwiadi (Program Pascasarjana, 2016)
This research aimed to build specific agroedutourism model for elementary school students in Malang Raya. Target of this research were 5th grade students from SDN Ketawanggede 2, SDN Sumberngepoh 02 and SDI Surya Buana. We provided three agroedutourism programs, there were 1). Learning on farmer’s friends and enemies, 2). Learning on plants as raw material for biopesticide and natural attractant and 3). Learning on healthy agroecosystem. Each agroedutourism program was composed by discussion, eco-games and taste of healthy foods. Data obtained by distributing questionnaires and analyzed by open source software, Smart PLS (Partial Least Square). Agroedutourism model from PLS output showed that learning on farmer’s friends and enemies program was the most effective to improve cognitive competence, enjoyment, pleasure, and the final-understanding of elementary school students than the other programs. While, initial-understanding directly contributing to improve cognitive competence and final-understanding of elementary school students. Cognitive competences directly influence to improve the student’s appraisal of foods that were obtained. Student enjoyment directly influence to affection and appreciation. Based on those models, to improve final-understanding, we had to improve initial-understanding using learning on farmer’s friends and enemies program. Students’ appreciation was improved by improving affection and appreciation.Keywords: agroedutourism, appreciation, cognitive, environmental awareness.